An annotated checklist of the endemic Apiaceae of Uzbekistan - Tojibaev, Komiljon Sh.; Beshko, Natalya Yu.; Turginov, Orzimat T.; Lyskov, Dmitry F.; Ukrainskaja, Uliana A.; Kljuykov, Eugene V. (Phytotaxa, 2020)
An annotated checklist of the endemic Apiaceae of Uzbekistan includes synonyms, references, information about geographic range, habitats and conservation status for each species. Distribution maps are provided. The number of endemic Apiaceae species in Uzbekistan was reduced from 38 to 18 as a result of new records in neighboring countries or because of their placement into synonymy. The new combination Galagania involucrata is published. Three new synonyms are established: Galagania neglecta under G. involucrata, Vvedenskya pinnatifolia under Conioselinum tataricum, and Elaeosticta seravschanica under E. paniculata. Five new species are recorded from the neighboring countries: Elaeosticta paniculata (Tajikistan), E. vvedenskyi (Kazakhstan), Eryngium octophyllum (Kyrgyzstan, Tajikistan), Ferula dshizakensis (Tajikistan) and Komarovia anisosperma (Tajikistan).